All That It Keeps Hidden: Rodell Warner, Archival Augmentations, and (Mis)Handling the Past - Charbonneau, Stephen (Imaginations)

(untitled) (York University, 2026)
Recent scholarship on interactive media has insisted we change how we talk about artificial intelligence (AI), preferring “collaborator” over “tool” as a descriptor of AI’s role in the creative process. This paper will consider such claims by centring the work of Trinidadian artist, Rodell Warner. Warner’s recent work in photography and digital media such as his series, “Augmented Archive,” has earned him several prestigious residencies and awards, particularly for his AI-generated interventions into the legacies of the colonial archive. His projects deploy digital technologies and machine learning to reimagine the visual archive and its frustrating gaps when it comes to representations of Caribbean peoples. The paper concludes with an assessment of the limitations of the “collaboration” argument – centring Warner’s artistic agency – while also arguing AI-generated art leaves one with a nagging melancholia that such technologies fail at decolonial redress while offering necessary, but insufficient radical visions.